1.
\(g(a)=a^3 +5a^2\)
\(\quad f(a)=2a+4 \)
\(\quad \text{Find } g(3)+f(3) \)
2.
\(f(x)=-3x^3 +3x\)
\(\quad g(x)=2x+5 \)
\(\quad \text{Find } f(-4) \div g(-4) \)
3.
\(g(a)=3a +3\)
\(\quad f(a)=2a-2 \)
\(\quad \text{Find } (g + f)(9) \)
4.
\(g(x)=4x+3\)
\(\quad h(x)=x^3 + 3x^2 \)
\(\quad \text{Find } (g-h)(-1)\)
5.
\(g(x)=x+3\)
\(\quad f(x)=-x+4 \)
\(\quad \text{Find } (g -f)(3) \)
6.
\(g(x)=-4x+1\)
\(\quad h(x)=-2x-1 \)
\(\quad \text{Find } g(5)+h(5) \)
7.
\(g(x)=x^2 +2\)
\(\quad f(x)=2x+5 \)
\(\quad \text{Find } (g-f)(0) \)
8.
\(g(a)=3x+1\)
\(\quad f(a)=x^3+3x^2 \)
\(\quad \text{Find } g(2) \cdot f(2) \)
9.
\(g(t)=t-3\)
\(\quad h(t)=-3T^3 +6t \)
\(\quad \text{Find } g(1)+h(1) \)
10.
\(f(n)=n-5\)
\(\quad g(n)=4n+2 \)
\(\quad \text{Find } (f+g)(-8)\)
11.
\(h(t)=t+5\)
\(\quad g(t)=3t-5 \)
\(\quad \text{Find } (h \cdot g)(5) \)
12.
\(g(a)=3a -2\)
\(\quad h(a)=4a+2 \)
\(\quad \text{Find } (g+h)(-10) \)
13.
\(g(n)=2n-1\)
\(g(n)=3n-5 \)
\(\quad \text{Find } h(0) \div g(0) \)
14.
\(g(x)=x^2 -2\)
\(\quad h(x)=2x+5 \)
\(\quad \text{Find } g(-6)+h(-6) \)
15.
\(f(a)=-2a - 4\)
\(\quad g(a)=a^2 + 3 \)
\(\quad \text{Find } \left(\frac{f}{g}\right)(7) \)
16.
\(g(n) = n^-3\)
\(\quad h(n)=2n-3 \)
\(\quad \text{Find } (g – h)(n) \)
17.
\(g(x)=- x^3 - 2\)
\(\quad h(x)= 4x \)
\(\quad \text{Find } (g – h)(x) \)
18.
\(g(x)=2x - 3\)
\(\quad h(x)=x^3 - 2x^2 + 2x \)
\(\quad \text{Find } (g – h)(x) \)
19.
\(f(x)= - 3x + 2\)
\(\quad g(x)= x^2 + 5x \)
\(\quad \text{Find } (f - g)(x) \)
20.
\(g(t)=t - 4\)
\(\quad h(a)= 2t\)
\(\quad \text{Find } (g \cdot h)(t) \)
21.
\(g(x)=4x + 5\)
\(\quad h(x)= x^2 + 5x \)
\(\quad \text{Find } g(x) \cdot h(x) \)
22.
\(g(t)= - 2t^2 – 5t \)
\(\quad h(t)=t + 5 \)
\(\quad \text{Find } g(x) \cdot h(x) \)
23.
\(f(x)=x^2 - 5x\)
\(\quad g(x)=x+5 \)
\(\quad \text{Find } ( f + g)( x ) \)
24.
\(f(x)=4x -4\)
\(\quad g(x)=3x^2 - 5 \)
\(\quad \text{Find } ( f + g)( x ) \)
25.
\(g(n)=n^2 + 5\)
\(\quad f(n)= 3n + 5 \)
\(\quad \text{Find } g(n) \div f(n) \)
26.
\(f(x)=2x + 4\)
\(\quad g(x)= 4x - 5 \)
\(\quad \text{Find } f(x) – g(x) \)
27.
\(g(a)=-2a +5\)
\(\quad f(a)=3a + 5 \)
\(\quad \text{Find } \left(\frac{g}{f}\right)(a) \)
28.
\(g(t)=t^3 + 3t^2 \)
\(\quad h(t)=3t - 5 \)
\(\quad \text{Find } g(3)+f(3) \)
29.
\(h(n) = n^3 + 4n\)
\(\quad g(n)=4n +5 \)
\(\quad \text{Find } h(n) + g(n) \)
30.
\(f(x)=4x +2\)
\(\quad g(x)=x^2 + 2x \)
\(\quad \text{Find } f(x) \div g(x) \)
31.
\(g(n)=n^2 - 4n\)
\(\quad h(n)= n - 5 \)
\(\quad \text{Find } g(n^2) \cdot h(n^2) \)
32.
\(g(n)=n + 5\)
\(\quad f(a)=2n - 5 \)
\(\quad \text{Find } (g\cdot h)(-3n) \)
33.
\(f(x)=2x\)
\(\quad g(x)= -3x -1 \)
\(\quad \text{Find } (f+g)( -4 -x) \)
34.
\(g(a)=-2a\)
\(\quad h(a)=3a \)
\(\quad \text{Find } g(4a) \ frac h(4a) \)
35.
\(f(t)=t^2 + 4t\)
\(\quad g(t)=4t + 2\)
\(\quad \text{Find } f(t^2) + g(t^2) \)
36.
\(h(n)=3n - 2\)
\(\quad g(n)=- 3n^2 – 4n \)
\(\quad \text{Find } g(3)+f(3) \)
37.
\(g(a)=a^3 + 2a\)
\(\quad h(a)=3a+4 \)
\(\quad \text{Find } (g \div h) (3) \)
38.
\(g(x)=- 4x + 2 \)
\(\quad h(x)=x^2 - 5 \)
\(\quad \text{Find } g(x^2)+h(x^2) \)
39.
\(f(n) = -3n^2 + 1\)
\(\quad g(n)= 2n + 1 \)
\(\quad \text{Find } (f – g)(n \ frac 3) \)
40.
\(f(n)=3n + 4 \)
\(\quad g(n)=n^3 – 5n \)
\(\quad \text{Find } f(n \div 2) - g(n \div 2) \)
41.
\(f(x)=- 4x + 1\)
\(\quad g(x)= 4x + 3 \)
\(\quad \text{Find } ( f \circ g) (9)\)
42.
\(g(x)=x - 1\)
\(\quad \text{Find } ( g \circ g) (7)\)
43.
\(h(a)=3a + 3\)
\(\quad g(a)=a + 1 \)
\(\quad \text{Find } (h \circ g) (5) \)
44.
\(g(t)=t + 3\)
\(\quad h(t)=2t -5 \)
\(\quad \text{Find } (g \circ h) (3) \)
45.
\(g(x)=x + 4 \)
\(\quad h(x)=x^2 -1 \)
\(\quad \text{Find } (g \circ h ) (10) \)
46.
\(f(a)=2a-4\)
\(\quad g(a)=a^2+2a \)
\(\quad \text{Find } (f \circ g)(-4) \)
47.
\(f(n)=-4n+2\)
\(\quad g(n)=n+4 \)
\(\quad \text{Find } (f \circ g)(9) \)
48.
\(g(x)=3x+4\)
\(\quad h(x)=x^3+3x\)
\(\quad \text{Find } (g \circ h)(3) \)
49.
\(g(x)=2x-4\)
\(\quad h(x)= 2x^3+4x^2\)
\(\quad \text{Find } (g \circ h)(3) \)
50.
\(g(a)=a^2+3\)
\(\quad \text{Find } (g \circ g)(-3) \)
51.
\(g(x)=x^2-5x\)
\(\quad h(x)=4x+4 \)
\(\quad \text{Find } (g \circ h)(x) \)
52.
\(g(a)=2a+4 \)
\(\quad h(a)=-4a+5 \)
\(\quad \text{Find } (g \circ h)(a) \)
53.
\(f(a)=-2a+2\)
\(\quad g(a)=4a \)
\(\quad \text{Find } (f \circ g)(a) \)
54.
\(g(t)=-t-4\)
\(\quad \text{Find } (g \circ g)(t) \)
55.
\(g(x)=4x+4\)
\(\quad f(x)= x^3-1 \)
\(\quad \text{Find } (g \circ f)(x) \)
56.
\(f(n)=-2n^2-4n\)
\(\quad g(n)=n+2 \)
\(\quad \text{Find } (f \circ g)(n) \)
57.
\(g(t)=-x+5\)
\(\quad f(t)=2x-3 \)
\(\quad \text{Find } (g \circ f)(x) \)
58.
\(g(t)=t^3-t\)
\(\quad f(t)=3t-4 \)
\(\quad \text{Find } (g \circ f)(t) \)
59.
\(f(t)=4t+3\)
\(\quad g(t)=-4t-2 \)
\(\quad \text{Find } (f \circ g)(t) \)
60.
\(f(x)=3x- 4\)
\(\quad g(x)=x^3+2x^2 \)
\(\quad \text{Find } (f \circ g)(x) \)